Translating Technology in Africa. Volume 2: Technicisation - Riedke, Eva,; Rottenburg, Richard, (Social Sciences E-Books Online, Collection 2025., 2025)
This volume revisits one of the great challenges of our time - the global circulation of technology and the resulting technicisation. Together, the introductory essay and six case studies argue that while circulation inevitably leads to the global standardisation of some forms, successful technicisation depends on local appropriation that takes place in the interstitial zones of translation. These zones, characterised by their asymmetrical power relations, need to be constantly renegotiated, recreated, and maintained in order to sustain decolonial translations. The aim of this volume is to stimulate further experimental praxiographic studies of decolonial translation in processes of technicisation, and thereby ignite novel, forward-looking theoretical debates. Contributors are Sarah Biecker, Marc Boeckler, Jude Kagoro, Jochen Monstadt, Sung-Joon Park, Eva Riedke, Richard Rottenburg, Klaus Schlichte, Jannik Schritt, Alena Thiel, Christiane Tristl, Jonas van der Straeten.